2010
DOI: 10.3732/ajb.1000247
|View full text |Cite
|
Sign up to set email alerts
|

Unique calcium oxalate "duplex" and "concretion" idioblasts in leaves of tribe Naucleeae (Rubiaceae)

Abstract: Crystal types appear to be systematic features in Naucleeae. Duplex idioblasts (CS and druses) and aggregate concretions are a demonstration that much is yet to be discovered about crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 17 publications
5
50
0
Order By: Relevance
“…Excess calcium is frequently precipitated in calcium salts such as oxalate, carbonate, silicate, sulfate, phosphate, citrate and malate (Weiner and Dove, 2003). Crystals have been identified in several studies as calcium oxalate by using EDS (Lersten and Horner, 2011;He et al, 2012;Raman et al, 2014). However, a small number of studies have indicated crystals formed by calcium sulfate (Storey and Thomson, 1994;He et al, 2012).…”
Section: Resultsmentioning
confidence: 97%
“…Excess calcium is frequently precipitated in calcium salts such as oxalate, carbonate, silicate, sulfate, phosphate, citrate and malate (Weiner and Dove, 2003). Crystals have been identified in several studies as calcium oxalate by using EDS (Lersten and Horner, 2011;He et al, 2012;Raman et al, 2014). However, a small number of studies have indicated crystals formed by calcium sulfate (Storey and Thomson, 1994;He et al, 2012).…”
Section: Resultsmentioning
confidence: 97%
“…Morphologically, the crystals are classified into five major forms: crystal sand, raphide, druse, styloid and prismatic (Franceschi and Horner 1980; Franceschi and Nakata 2005; Horner and Wagner 1995) and each category of crystal may show variations in its shape and size. Studies of the types of crystals and their macropatterns are species and genus specific and may contribute to understanding phylogenetic relationships (Horner et al 2012; Lersten and Horner 2000; 2011; Prychid and Rudall 1999). The formation of calcium oxalate crystals in plants is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…By individually sequencing these homoeologs in allopolyploids, using either specific primers, single-molecule (sm) polymerase chain reaction (PCR) (see Kraytsberg and Khrapko 2005), or in vivo cloning (reviewed in Brysting et al 2011), reticulate organism phylogenies can be untangled (e.g., Popp and Oxelman 2001; Sang 2002; Smedmark et al 2003; Howarth and Baum 2005; Popp et al 2005; Huber et al 2006; Brysting et al 2007; Popp and Oxelman 2007; Fortune et al 2008; Kim et al 2008; Mason-Gamer 2008; MandĂĄkovĂĄ et al 2010; Marcussen et al 2011; Brysting et al 2011). The raw data are a set of multilabeled trees (or MUL trees), i.e., gene trees that contain more than one sequence for some of their included species as a result of gene duplication (paralogy) and/or polyploidy (homoeology), and these are then transformed into a species network.…”
mentioning
confidence: 99%
“…The cosmopolitan genus Viola (Violaceae), with 500–600 species of violets and pansies, comprises numerous hybrid and polyploid complexes in the northern hemisphere (Miyaji 1913; Moore and Harvey 1961; Clausen 1964; Fabijan et al 1987; Ballard et al 1998; Nordal and Jonsell 1998; van den Hof et al 2008; @x Hepenstrick 2009; Marcussen et al, 2011). From a putative base number of x = 6 or x = 7, extant chromosome numbers range from dysploid 2 n = 4 in V. modesta , the lowest number known in angiosperms and also found in five other genera unrelated to Viola and Violaceae, to at least 20-ploid 2 n = ca.…”
mentioning
confidence: 99%